What is the best way to communicate the uncertainty of a digital soil mapping product? Some lessons from an end-users survey - Léa Courteille; Léa Tardieu; Nadia Boukhelifa; Evelyne Lutton; Philippe Lagacherie (Geoderma)
Uncertainty in digital soil mapping products is generally quantified and presented alongside the predictions in the form of a second raster map. However, it remains a challenge for end-users to integrate this additional information into their decision-making, and as a result, they tend to ignore uncertainty. The Digital Soil Mapping (DSM) literature has identified two levers for better communicating uncertainty: uncertainty representations that allow users to integrate uncertainty better than with a separate raster map, and spatial aggregation, which consists of representing the spatial information at a coarser resolution to reduce its uncertainty. For the first time in DSM, we involved a large number of end-users (263 people) via a web-based survey to evaluate alternative cartographic representations of soil map uncertainty. Respondents were assigned a decision-making task and asked to select the map that offered the best support, choosing between two maps that displayed the same soil information but differed in how uncertainty was represented and/or in the level of spatial aggregation. The choices made by the respondents as well as the comments they left at the end of the study provided a large dataset from which we could identify factors driving their preferences. We demonstrate that end-users strongly prefer uncertainty to be shown on a separate map, and also favor moderately aggregated maps. Our results question the conventional representation of soil data using high-resolution and high-uncertainty maps. We hope that this work will be valuable to scientists in soil science, as well as in other environmental mapping communities, such as ecosystem services and biodiversity, and help them more effectively communicate uncertainty to their end-users.